Optimization of endospore production by solid and liquid fermentation for the development of effective formulations of Bacillus velezensis-based products - Duré, Laís Mayara Melo [UNESP]; Mascarin, Gabriel Moura; Bettiol, Wagner [UNESP] (Springer Nature, 2025)
The objective of this study was to optimize the culture medium for enhanced production of Bacillus velezensis AP-3 endospores using both liquid and solid-state fermentation techniques. Additionally, the study aimed to assess the stability of endospores in powder formulations containing talc and potato starch, and to evaluate the growth-promoting effects of these formulations on bean plants. Further, we evaluated the inhibition of mycelial growth of Sclerotinia sclerotiorum and Fusarium oxysporum f. sp. lycopercisi by metabolites produced by this bacterial strain. The plant growth promotion assay evaluated these formulations across various application methods: seed treatment, sowing furrow application, and a combination of both. Adjustments to culture medium significantly influenced the endospore yield of B. velezensis. Solid-state fermentation in rice flour and potato starch yielded up to 2.06 × 108 and 1.82 × 108 CFU g− 1 after 7 days in a 60% moisture medium, respectively. Conversely, submerged fermentation in molasses + cottonseed flour medium produced 1.7 × 109 CFU mL− 1 (viable endospores) in 3 days. The powder formulations showed high stability, maintaining viability for up to 226 days at room temperature. This bacterial strain effectively inhibited the mycelial growth of target fungal pathogens and promoted bean plant growth, particularly by enhancing root development. These findings highlight the versatility of B. velezensis AP-3 in producing endospores through two fermentation methods, its extended shelf-life as a wettable powder formulation, and its efficacy both as biocontrol agent and plant growth promoter, contributing to a sustainable agriculture.
Keywords: Antibiosis; Biological control; Fermentation; Plant growth promotion; Wettable powder